Efficacy of Homeopathy in the Multiphase Management of Migraine (Homoeopathy for All, 2024)
Migraine is the sixth most disabling  and the third most prevalent illness  globally, affecting approximately  1 billion individuals.1 This  neurological condition manifests as  intense throbbing headaches often  accompanied by nausea, vomiting,  and sensitivity to light and sound.  Such symptoms significantly impair  quality of life, reducing productivity  and increasing medical expenditure.  In the U.S., about one in four  people experiences migraines,  with 18% of women, 6% of men,  and 10% of children affected. In  India, the prevalence of migraine is  reported to be around 25% among  women and 10% among men.2 Key  triggers include stress, weather  changes, exhaustion, certain foods  and beverages, sleep disturbances,  hunger, and hormonal fluctuations.3 Understanding these factors is  crucial for effective management  and prevention.
Keywords: Homeopathic remedies; General Management; preventive